APPLICATION OF THE INDEPENDENT CURRICULUM TOWARDS LEARNING OUTCOMES OF CLASS IV STUDENTS IN MATHEMATICS LESSONS IN PRIMARY SCHOOL 57 BANDA ACEH - Fitria, Husnul; Darnius, Said; Fauzi, Fauzi (Elementary Education Research, 2023)
The implementation of the Independent Curriculum is one of the ways implemented by the government to improve the quality of education in Indonesia, through the implementation of the Independent Curriculum teachers are expected to be able to improve student learning outcomes on the topic of learning mathematics. Until now the implementation of the Independent Curriculum has not been known to what extent the ability of students in grade IV SD to learn mathematics. The formulation of the research problem is "How is the implementation of the independent learning curriculum in the process of learning mathematics at SD Negeri 57 Banda Aceh?" The purpose of this study was to identify and obtain information about the implementation of the independent learning curriculum in mathematics at SD Negeri 57 Banda Aceh, and to further investigate student learning outcomes when learning mathematics with the application of the independent learning curriculum at SD Negeri 57 Banda Aceh. Research with a qualitative approach, for this type of research is descriptive. The research was conducted at SD Negeri 57 Banda Aceh, Syiah Kuala District, Banda Aceh City. The subject of this study was the fourth grade teacher and all fourth grade students at SD Negeri 57 Banda Aceh totaling 27 students. Data was collected by means of interviews and documentation. By choosing the Miles and Huberman model, in which data analysis consists of three streams of activities that occur simultaneously, namely: data reduction, data presentation, and drawing conclusions. From the results of interviews and documentation, it shows that the implementation of the Independent Curriculum has been running in accordance with school policies but there is still a need for teacher training on the PJBL model and the Minimum Competency Assessment (AKM), and student learning outcomes in mathematics learning material are in the good category, meaning that they have not shown significant difference with the implementation of the previous curriculum. The results obtained from interviews and documentation of fourth grade students at SD Negeri 57 Banda Aceh with the implementation of the independent curriculum in mathematics are in the good category.